2007
DOI: 10.1074/jbc.m611259200
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Enhances Syndecan-1 Shedding

Abstract: When shed from the cell surface, the heparan sulfate proteoglycan syndecan-1 can facilitate the growth, angiogenesis, and metastasis of tumors. Here we report that tumor cell expression of heparanase, an enzyme known to be a potent promoter of tumor progression and metastasis, regulates both the level and location of syndecan-1 within the tumor microenvironment by enhancing its synthesis and subsequent shedding from the tumor cell surface. Heparanase regulation of syndecan-1 is detected in both human myeloma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
145
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 237 publications
(159 citation statements)
references
References 31 publications
11
145
1
2
Order By: Relevance
“…We previously demonstrated that heparanase enhances syndecan-1 shedding in both myeloma and breast cancer cells and that elevated levels of syndecan-1 in the myeloma tumor microenvironment drives tumor angiogenesis, metastasis and growth (7,36,37). In addition to enhancing syndecan-1 shedding, elevation of heparanase diminishes localization of syndecan-1 in the nucleus (21).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that heparanase enhances syndecan-1 shedding in both myeloma and breast cancer cells and that elevated levels of syndecan-1 in the myeloma tumor microenvironment drives tumor angiogenesis, metastasis and growth (7,36,37). In addition to enhancing syndecan-1 shedding, elevation of heparanase diminishes localization of syndecan-1 in the nucleus (21).…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfate chains from the shed syndecan-1 were removed by addition of 5 milliunits/ml heparinase III (Seikagaku, Kogyo, Japan) at 37°C for 2 h. Levels of shed syndecan-1 were determined by ELISA as described previously (4). Experiments also included depletion of heparin-binding growth factors such as HGF from the conditioned media by incubating overnight at 4°C with 25 l of heparin immobilized on agarose (MP Biomedicals, Solon, OH).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its enzymatic glycosidase activity, various nonenzymatic roles of heparanase such as enhancement of AKT signaling have also been described (2). In multiple myeloma, data from in vitro and in vivo models coupled with analysis of clinical samples have identified heparanase as a promoter of tumor angiogenesis, growth, and metastasis (3)(4)(5)(6)(7). Together these findings indicate that heparanase is a key regulator of myeloma progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been identifi ed that syndecan-1 can be shed by heparanase from the cell surface (Yang et al, 2007) via stimulation of ERK that leads to MMP-9, a syndecan-1 sheddase, expression (Purushothaman et al, 2008). A more recent study indicated that heparanase also regulates levels of syndecan-1 in the nucleus (Chen and Sanderson, 2009).…”
Section: Soluble Syndecans and Tumormentioning
confidence: 99%